Fist of the North Star. Volume 8 - Buronson, 1947- (Viz signature., 2023)
"In a postapocalyptic world, humanity has risen from the ashes of all-out nuclear war to a nightmare of endless suffering. It is a time of chaos. Warlords and gangs of savage marauders rule the broken ruins of civilization, terrorizing and enslaving the survivors. Life has become a brutal struggle for existence and death the only release. Kenshiro takes on Holy Emperor Souther, the most powerful of the Six Holy Fists of the South Star. If Kenshiro defeats him, it will set up a fateful battle between Raoh and Toki--a confrontation between motion and stillness, of ferocity and serenity--in which neither master will yield an inch. Shichosei, the star that presages death, shines overhead as Toki unleashes what could be his final strike"--Cover.